Das Kašteli Caelius Mons (Kellmiinz an der lller) - eine tetrarchische Festungsbaumafinahme in der Provinz Raetien - Mackensen, Michael (Arheološki vestnik, 1994)
Until recently a connection vvas regarded as probable betvveen the inscription of A.D. 281 found at Augsburg, commemorating the emperor Probus as [restitutor prjovinciarum et operum [publicoriim] and the construction of nevv military fortifications in Raetia along the river Iller and the upper Danube. From 1986 to 1991 excavations vvere carried out in the castellum Caelius Mons (Kellmiinz upon Iller), a fort of 0,86 ha in size, vvhere according to the Notitia Dignitatum occ. XXXV,30 the cohors III Herculea Pannoniorum vvas garrisoned. The fort gateway as vvell as the projeeting corner- and interval-tovvers vvere investigated and a ground-plan including the topographically adjusted north- and south-vvest corners reconstructed. The evidence of tvvo unvvorn and little-circulated coins found under a mortar floor shovvs that the earliest vvooden buildings (vvhich are shovvn to be earlier than the stone fort) cannot be dated earlier than A.D. 297 (period 1). Not much later the fort vvith its stone vvall and a double diteh in front ofthe east vvall vvas constructed (period 2); fairly soon the interior vvooden buildings bumt dovvn around A.D. 300/303. Within the province of Raetia the castellum Caelius Mons and the forts at Gundremmingen (Biirgle). Burghofe and Eining are Tetrarchic fortifications built during the last years ofthe 3rd century.